The Balance-of-Payments Deficit and the Tax Structure - Salant, Walter S. (The Review of Economics and Statistics, 1964)
good deal of emphasis has also been placed, however, on the claimed benefits of such a shift to the United States balance-of-payments position. For example, the CED statement goes on to say that, A major advantage of a general excise tax is that it would tend to improve the ability of the United States to compete with others in world markets. This view assumes that the direct tax that is cut is the corporate profits tax and that a cut in it reduces prices of corporate output. The present paper calls to attention some influences that are frequently neglected in appraising the effects of such a shift on the balance of payments when these assumptions are valid. It then considers the effects of a cut in corporate taxes that does not reduce prices. Finally, it considers the balance-of-payments effects of making the cut in direct taxes in the individual income tax.